Effect of Different Harvest Ages on Alginat ContentiIn Seaweed Sargassum sp Using the Longline - Supiandi, Supiandi; Cokrowati, Nunik; Lestari, Dewi Putri (Program Studi Budidaya Perairan Universitas Mataram, 2023)
Sargassum sp. seaweed. It is a type of seaweed that has high economic value because of its alginate content and has the greatest and abundant potential in Indonesia. The alginate content produced in the seaweed Sargassum sp. Influenced by the harvest age in the cultivation process, if it is harvested too early, low quality seaweed will be produced and the older the harvest, the higher the alginate content. To obtain good alginate content, namely by knowing the optimal harvest age in cultivation. The aim of this research is to determine the effect of different harvest ages in seaweed (Sargassum sp.) on the alginate content using the Long line cultivation method. This research was conducted in Ekas Bay, Ekas Buana Village, Jerowaru District, East Lombok, West Nusa Tenggara. This research was carried out using an experimental method using a completely randomized design (CRD), which consisted of 5 treatments by weight of Sargassum sp. namely P1 28 days of harvest, P2 35 days of harvest, p3 of 42 days of harvest, p4 of 45 days of harvest, p5 of 59 days of harvest. Cultivation using seeds weighing 100 grams was then analyzed for alginate content. The results of this study indicate that the age of harvest affects the alginate content and weight growth of the seaweed sargassum sp. the best treatment was found in the p4 treatment with an alginate content value of 1.14% and the lowest in the p1 treatment of 0.76%. The conclusion of this study is that the different harvesting ages of Sargassum sp which were reared using the long line method showed an effect on the alginate content of Sargassum sp. the best treatment was found in p4 because it showed the highest value of alginate content and growth weight.